Strategy of the Inclusion Community Empowerment with â€œTepatâ€ Product Service in BTPN Syariah of Nganjuk - Laksono, Sonny SM (Prosiding Seminar, 2022)
The development and/or development of Kediri's Dhoho Airport will have a broad impact on major changes in the economic aspects of the surrounding area. The purpose of this study is how the development of BUM Desa in Tarokan Subdistrict, efforts to develop BUM Desa that need to be carried out in Tarokan Subdistrict, policies and programs for developing BUM Desa in Tarokan Subdistrict. 10 (ten) villages, all of which have established BUM Desa. The collection of data and/or information is carried out through document studies, observation, interviews, focus group discussions, and is complemented by library research. The results of the first study, the development of BUM Desa in Tarokan District has not shown results in accordance with the mandate of Law Number 6 of 2014, namely: improving the village economy, improving community welfare, and increasing Village Original Income (PADesa). Second, efforts to develop BUM Desa in Tarokan Subdistrict need to be focused on aspects: the legal entity status of BUM Desa; capital; type of business; and governance or management. Third, it is necessary to immediately enact: (1) Regent's Decree concerning the Establishment of the Coordination Team for Development of Village Owned Enterprises (BUMDes) in Tarokan District and the Secretariat of the Coordination Team for Development of Village Owned Enterprises (BUMDes) in Tarokan District; and (2) the establishment of a Technical Implementation Unit (UPTD) for Community Empowerment and Village Administration in Tarokan District.